The Evidence of Cooperative Binding of a Ligand to G4 DNA - A. G. Kudrev (Journal of Analytical Methods in Chemistry)
Intrinsic constants of the ligand binding with G4 DNA (guanine-rich DNA sequence) using quantitative standards can be convenient providing the assessment for elucidating the possibility of such structures participation in biochemical processes. In the present communication, the hard + soft modelling approach to calculate intrinsic constants of a ligand binding with short DNA molecule, particularly such as G4 DNA, has been proposed. The suggested approach has focused upon the quantitative evaluating of a mutual influence between sites and between bound ligands. The cross-validation between a new hard + soft modelling and conventional stepwise complex formation algorithm has been conducted. A number of simulated examples will illustrate the methodology. The experimental mole-ratio titration of TMPyP4 by G4 DNA [(CG3)2CGC(AG3)2G] has been reexamined. The [(CG3)2CGC(AG3)2G] that folds from a G-rich sequence found in the promoter region of c-kit oncogene can be considered as a molecule with two equivalent mutually influence binding sites.